COMPARISON OF PERFORMANCE OF SYNCHRONIZATION ALGORITHMS FOR GRID CONNECTED POWER ELECTRONICS CONVERTERS ACCORDING TO PROPOSED EVALUATION QUALITY CRITERIA - Lipnicki, Piotr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
In this paper a comparison of synchronization methods for power electronics converters is presented. Proposed evaluation criteria are based on Transmission System Operators requirements, as well as on criteria parameters based on requirements for design, computation and operation under normal/distorted conditions. Additionally a classification of various kinds of synchronization algorithms is discussed with a brief description of the role of power electronics in the modern power systems. All of the tested algorithms were subjected to appropriate tests validating the quality criteria for each of them. The tests were performed in terms of simulations. The investigation results are summarized in the table, which can serve as a basic selection guide.